2019
DOI: 10.3390/su12010054
|View full text |Cite
|
Sign up to set email alerts
|

Choice Behavior of Autonomous Vehicles Based on Logistic Models

Abstract: To understand the public's acceptance of autonomous vehicles, studies were conducted from the perspectives of personal attributes, travel demand and cognitions of autonomous vehicles based on 403 valid questionnaires. Influencing factors of whether travelers are purchasing autonomous vehicles, whether travelers without a driver's license intend to take a driver's license in the future and whether travelers are choosing an autonomous private car if travelers can only take a taxi or drive a private car are analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…A number of studies that have investigated public opinion about AVs have been conducted over the last decade. Recently, studies have been conducted on perceptions of shared autonomous vehicles and self-driving taxis, and on preferences among innovative modes of transportation [5][6][7][8]. However, under and post-COVID-19 circumstances, people are more sensitive to sanitation and quarantine measures, so they prefer autonomous private vehicles to modes of transportation that require sharing a vehicle with others [8,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies that have investigated public opinion about AVs have been conducted over the last decade. Recently, studies have been conducted on perceptions of shared autonomous vehicles and self-driving taxis, and on preferences among innovative modes of transportation [5][6][7][8]. However, under and post-COVID-19 circumstances, people are more sensitive to sanitation and quarantine measures, so they prefer autonomous private vehicles to modes of transportation that require sharing a vehicle with others [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, there is a growing interest in not only autonomous private vehicles, but also various new modes of transportation, including shared autonomous vehicles and self-driving taxis. Acceptance and preference for each mode of transportation are actively being studied [5][6][7][8]. However, in the current COVID-19 pandemic, people prefer personal autonomous vehicles over other types of transportation because of sanitation and the reduced risk of contagion [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Cox and Snell R 2 (like R 2 in linear regression model) describes the portion of the variation in the outcome which is explained by the independent variables. [87]. In the next step, the cluster analysis categorized participants into two homogenous groups in terms of sense of place (see Table 10 and Figure 4).…”
Section: Analysis Methodsmentioning
confidence: 99%
“…The factors studied by other researchers includes age, trip purpose, catchment area, main haul length/time, population density, access-egress time, socio-economic conditions and few other parameters (Goel & Tiwari, 2016;Krygsman et al, 2004;Tan et al, 2020). It is concluded that access-egress characteristics varies significantly across different socioeconomic and demographic conditions (Ribeiro et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%